Electrophysiological effects of monoamine oxidase inhibition on rat midbrain dopaminergic neurones: an in vitro study. - Mercuri, N. B. (1996)
1 The effects of the inhibition of monoamine oxidase (MAO) type A and B have been evaluated on the spontaneous firing activity of the dopaminergic (principal) neurones of the rat midbrain intracellularly recorded from a slice preparation. 2 The non-specific MAO inhibitor, pargyline, superfused at a concentration of 10-100 microM, decreased or abolished the spontaneous firing discharge of the principal neurons in the subtantia nigra pars compacta and ventral tegmental area. This effect had a slow onset and appeared to be sustained. 3 The administration of the dopamine D2/3 receptor antagonist, sulpiride (100-300 nM), antagonized the pargyline-induced effect, while the superfusion of the dopamine D1 receptor antagonist, SCH 23390 (1-3 microM) did not counteract the induced inhibition of the firing rate. 4 The inhibitor for the MAO A, clorgyline (30-100 microM), reduced the firing rate of the dopaminergic neurones. A similar depressant effect was also observed when a MAO B inhibitor, deprenyl (30-100 microM), was applied. Lower concentrations of both drugs (300 nM-10 microM) did not produce consistent effects on neuronal discharge. 5 Our data suggest that only the blockade of both types of MAO enzymes favours the inhibitory action of endogenous dopamine on somato-dendritic D2/3 autoreceptors.